Development of films from natural sources for infections during wound healing - Leyva-Gómez, Gerardo; González-Torres, Maykel; Alcalá-Alcalá, Sergio; Bernal-Chávez, Sergio A.; Morales-Morfin, Juan C.; González-Del Carmen, Manuel; Sharifi-Rad, Javad; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; Del Prado-Audelo, María Luisa; Cortés, Hernán (Cellular and Molecular Biology, 2021)
The skin is the largest organ in the human body, and due to its barrier function, it is susceptible to multiple injuries. The appearance of infections during the wound healing process is a complication that represents a formidable hospital challenge. The presence of opportunistic bacteria with sophisticated resistance mechanisms is difficult to eradicate and compromises patients' lives. Therefore, the search for new efficacious treatments from natural sources that prevent and counteract infections, in addition to promoting the healing process, has increased in recent years. In this respect, films with the capability to protect wounds and release drugs are the presentation that predominates commercially in the hospital environment. Those films can offer several mechanical advantages such as physical protection to prevent opportunistic bacteria's entry, regulation of gas exchange, and capture of exudate through a swelling process. Wound dressings are generally curative materials easily adaptable to different anatomical regions, with high strength and elasticity, and some are even bioabsorbable. Additionally, the components of the films can actively participate in promoting the healing process. Even more, the film can be made up of carriers with other active participants to prevent and eradicate infections. Therefore, the extensive versatility, practicality, and usefulness of films from natural sources to address infectious processes during wound healing are relevant and recurrent themes. This work presents an analysis of the state-of-the-art of films with natural products focused on preventing and eradicating infections in wound healing.